Addition Of D-Sorbitol Improves The Usability Of Ophthalmic Viscosurgical Devices - Watanabe I (Dove Medical Press, 2019)
Ippei Watanabe,1 Mayumi Nagata,2 Hiroyuki Matsushima2 1Medical Science Liaison Unit, Seikagaku Corporation, Tokyo, Japan; 2Department of Ophthalmology, Dokkyo Medical University, Tochigi, JapanCorrespondence: Ippei WatanabeMedical Science Liaison Unit, Seikagaku Corp., 6-1, Marunouchi 1-chome, Chiyoda-ku, Tokyo 100-0005, JapanTel +81 3 352208595Fax +81 3 352208975Email ippei.watanabe@seikagaku.co.jpPurpose: To evaluate the effects of D-sorbitol addition on changes in the extrusion force of ophthalmic viscosurgical devices (OVDs).Methods: OVD formulations; the mixtures of 3% hyaluronic acid (HA) and 4% chondroitin sulfate (CS) containing 0%, 0.5%, or 1.0% D-sorbitol were prepared. Each prefilled syringe of OVD was stored at room temperature for 0, 15, 30, 60, or 120 mins after a small amount of viscoelastic agent was discharged from the needle. The extrusion force values (kgf) of these OVDs when reused after storage were measured with a texture analyzer. Moreover, 10 healthy adults (5 men and 5 women) used a pinch sensor to measure the extrusion force values for the HA/CS combination without D-sorbitol which was stored in the above manner, and used a 4-step scale to score the usability of OVD.Results: For the HA/CS combination without D-sorbitol, the extrusion force value was increased from its initial value (storage duration, 0 min) as storage duration increased. However, for the HA/CS combination containing 0.5% or 1.0% D-sorbitol, this value remained almost unchanged over time. Likewise, the pinch sensor-determined extrusion force values of HA/CS combination without D-sorbitol increased, depending on storage duration.Conclusion: The addition of D-sorbitol to viscoelastic agent may suppress the needle clogging that occurs with OVD storage, and may improve the usability of OVDs during surgery.Keywords: ophthalmic viscosurgical device, extrusion force, cataract surgery, vitreous surgery